KAJIAN PEMBERIAN KOMPOS DARI KULIT BUAH KAMANDRAH TERHADAP PERTUMBUHAN BIBIT TANAMAN KAMANDRAH (Croton tiglium L.) YANG DITANAM PADA TANAH BEKAS TAMBANG (Study of Kamandrah Rind Composting on the Growth of Kamandrah (Croton tiglium L.) Seedlings Planted on Former Mining Soil) - I Nyoman, Sudyana,; putera, Sa; liansyah, Mu; Titin Apung, Atikah (Universitas Palangka Raya, 2015)
ABSTRAKThe purpose of this study was to determine the effect of increasing doses of kamandrah rindcomposting on the growth of kamandrah seedlings planted on former mining soil. The materials usedfor this study were kamadrah seeds taken from Tamiang, dolomite lime, compost , polybag, formermining soil, wood, nail and and gauze. The tools used were scales, hoes, machetes, yells, sieves, andother stationeries. This study simply employed a Completely Randomized Design (CRD) with 4 levelsof treatment K0 (control), K1 (composting with 2 t / ha), K2 (composting with 4 t / ha) and K3(composting with 6 t / ha). The series of experiments for each level of treatment was repeated for sixtimes, so that the overall result were 24 experimental units. The results showed that the compostingapplication of kamandrah seedlings has a significant effect on the height of plant, the number ofleaves, the seedlings. The of kamandrah rind composting was best applied on the treatment of K2 thatresulted in 14,11 cm for the height of the plant, 9.71 for the number of leaves, 9.26 g for the freshweight and 1.36 g for the dry weight of the fruits, those were higher than the other treatments .Key word : Kamandrah, compost, Nurseries, former mining soil